Contribution of ROB-1 and PBP3 mutations to the resistance phenotype of a β-lactamase-positive amoxicillin/clavulanic acid-resistant Haemophilus influenzae carrying plasmid pB1000 in Italy. - San Millan, A; Giufré, M; Escudero, J; Hidalgo, L; Gutierrez, B; Cerquetti, M; Gonzalez-Zorn, B (2011)
OBJECTIVES: plasmid pB1000 bearing bla(ROB-1) is responsible for high-level β-lactam resistance in Haemophilus influenzae as well as in Pasteurella multocida and Haemophilus parasuis isolates from Spain. Here, we explore the presence of ROB-1 in Italy and investigate the relative contribution of penicillin-binding protein 3 (PBP3) mutations and ROB-1 to the β-lactam resistance phenotype in H. influenzae. METHODS: the collection of the Italian Reference Laboratory of H. influenzae was investigated for ROB-1-positive isolates between 2004 and 2009. H. influenzae Rd KW20 was used as recipient for pB1000 electroporation and for mutagenesis of the ftsI gene encoding PBP3. RESULTS: the presence of plasmid pB1000 in a non-typeable H. influenzae isolated in Italy, BB1059, is reported in this work. This strain is not genetically related to the H. influenzae clinical isolates bearing pB1000 described in Spain. The sequence of ftsI from BB1059 revealed several mutations in the predicted amino acid sequence of PBP3. To determine the relative contribution of pB1000 and PBP3 mutations to the β-lactam resistance phenotype of BB1059, H. influenzae Rd KW20 was transformed with ftsI and/or pB1000 from BB1059. β-Lactam resistance profiles revealed the additive effect of pB1000 and PBP3 mutations conferring resistance to β-lactams, including amoxicillin/clavulanic acid and third-generation cephalosporins. CONCLUSIONS: intra-European spread of plasmid pB1000 among H. influenzae has been shown. The coexistence of plasmid pB1000 and mutations in PBP3 produces an additive resistance phenotype in H. influenzae.